Training loads and incidence of injury during the preseason in professional rugby league players - Killen, N. M; Gabbett, T. J.; Jenkins, D. G. (The Journal of Strength and Conditioning Research, 2010)
Research into rugby league has found a significant, positive relationship between training load and injury rates. However, there has been limited research investigating this relationship in the preseason period, and the relationship between training load, and injury among professional rugby league players is yet to be examined. The primary aim of this study was to examine the relationships between training load, various psychological data, and the incidence of injury during preseason training at a professional rugby league club. Thirty-six male professional rugby league players undertook a 14-week training program. Each player's training time, intensity rating, and injury status were recorded after each training session. In addition, players rated their sleep, food, energy, mood, and stress on a scale of 1-10 (with 1 being extremely poor and 10 being excellent) biweekly. Over the entire preseason period, a total of 2,877.9 training hours were recorded for the players, with an overall incidence of injury of 6.9 per 1,000 training hours. Higher training loads during the first half of the preseason corresponded to a higher injury rate in comparison to the second half of the preseason. No significant relationship was found between the preseason weekly injury rate and the weekly load, nor was there a relationship between injury and psychological data. These findings suggest no relationship between training load, psychological data, and injury incidence during the preseason training period in professional rugby league players. However, results suggest that players may have an increased risk of injury during the early preseason period. The findings of this study may be particularly useful in professional rugby league teams to determine when a player is at increased risk of injury, using their training loads and psychological data.